Effects of SiC and Mg co-addition on the superconducting and microhardness properties of MgB2 - Tran, Duc H.; Nhan, Duong T.T.; Pham, An T.; Nam, Nguyen Hoang; Thuy, Kieu Xuan; Le, Tien; Le, Viet Cuong; Hong, Vuong T.A.; Lee, Hannoh; Park, Tuson; Peh, Hoo-Keong; Chen, Soo-Kien; et al. (Elsevier, 2025)
This study investigates the role of 0.5 mol Mg in combination with varying weight percentages of SiC to explore the impact on their overall performance of superconducting, mechanical properties of MgB2 material with a focus on its critical current density (Jc), critical temperature (Tc), flux pinning, upper critical field (Hc2) and Vickers hardness (Hv) behavior. Compared to pure MgB2, the self-field Tc, Jc and Hc2 is higher when Mg is added (sample MgB2 + 0.5 mol Mg). The results show that the Jc of the samples decrease as the SiC doping concentration increases. When comparing the Hc2 values with those of the pure sample, the MgB2 + 0.5 mol Mg sample exhibited the highest value. However, with the addition of SiC, the Hc2 values showed random variations. Tc and Hv parameters shown the same behavior. Vickers hardness measurements confirm that all samples demonstrated the reverse indentation size effect, indicating an increment in hardness values with an applied load across all samples. Further, the microindentation hardness measurements underwent semi-empirical analysis through several models. After comparison, the Indentation-Induced Cracking model is identified as the best fit, providing parameters that aligned most closely with the load-independent microhardness results.